2013
DOI: 10.3109/13880209.2013.823551
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofin silico, in vitroα-amylase inhibition potential and antidiabetic activity ofPterospermum acerifoliumbark

Abstract: The present study confirmed the antihyperglycemic activity along with its status on hepatic biomarkers, antihyperlipidemic and antioxidant properties of Pterospermum acerifolium bark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The inhibition constant (Ki) for this compound was estimated as 269.35 nmol with two hydrogen bond interactions, although there is no report on the evaluation of fucosterol and β-sitosterol against pancreatic α-amylase activity so far. [ 77 ] Taking together, anti-diabetic sterols of this algae may be responsible at least in part for anti-diabetic activity of Sargassum species. [ 46 ] However, this activity is supposed to be performed via different mechanisms, of which α-amylase inhibitory activity is one of the most critical ones.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition constant (Ki) for this compound was estimated as 269.35 nmol with two hydrogen bond interactions, although there is no report on the evaluation of fucosterol and β-sitosterol against pancreatic α-amylase activity so far. [ 77 ] Taking together, anti-diabetic sterols of this algae may be responsible at least in part for anti-diabetic activity of Sargassum species. [ 46 ] However, this activity is supposed to be performed via different mechanisms, of which α-amylase inhibitory activity is one of the most critical ones.…”
Section: Resultsmentioning
confidence: 99%
“…Trypsin inhibitor was previously isolated by Shee and Sharma (2007) from the seeds of Murraya koenigii which belongs to rutaceae family. Rathinavelusamy et al (2014) previously reported a protein with α-amylase inhibition potential and antidiabetic activity from the bark of Pterospermum acerifolium belonging to malvaceae family.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin inhibitor was previously isolated by Shee and Sharma (2007) from the seeds of Murraya koenigii which belongs to rutaceae family. Rathinavelusamy et al (2014) previously reported a protein with α-amylase inhibition potential and antidiabetic activity from the bark of Pterospermum acerifolium belonging to malvaceae family. Bijina et al (2011) observed that the crude extract of leaves of Moringa oleifera showed maximum percent of inhibition (77%) followed by the seed extract (63%).…”
Section: Discussionmentioning
confidence: 99%
“…Though the activity of (28) was adjudged good, the comparison was done at a very high concentration (20 mg/kg) of the test compound as against glibenclamide (0.3 mg/kg). In another in vivo multiple dose (15 and 30 mg/kg for 30 days) antidiabetic study of an ethyl acetate sub-fraction of an ethanol extract of the bark of Pterospermum acerifolium from which (28) was isolated, the authors reported good activity at 30 mg/kg of the fraction as against 0.6 mg/kg of STD drug used in the study (Rathinavelusamy et al 2014 ). It was not clear to us what the STD drug was in the article.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…It was not clear to us what the STD drug was in the article. Rathinavelusamy et al 2014 after isolating (28) from the most active fraction of Pterospermum acerifolium conducted an in silico antidiabetic study to determine the inhibitory activity of (28) against the human pancreatic α-amylase (HPA). They revealed free binding energy and inhibition constant (K i ) of − 8.39 kcal/mol and 0.269 µmol for (28) , and -6.07 kcal/mol and 28.52 µmol for the reference drug, acarbose, and they presented (28) as a potential HPA inhibitor when compared to acarbrose (Rathinavelusamy et al 2014 ).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%